Pengaruh Pemberian Imunisasi Intranasal Epitope Protein RrgB 255-270 Streptococcus pneumoniae Terhadap Kadar IL-4 - Widiatmaja, Danang Tejamukti; Mufida, Diana Chusna; Febianti, Zahrah (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Streptococcus pneumoniae or pneumococcus is the main cause of community acquired pneumoniae (CAP). Infection of pneumococcal can be prevented by vaccines, like PPV and PCV. Those vaccines have several weaknesses, like, limited to several strain of bacteria and invasive. Nowadays, development of pneumococcal vaccines used the antigenic component of which occur on the bacteria, like epitope. One of the epitopes that can be used as vaccine candidate is epitope from RrgB protein of bacteria’s pili. One of the RrgB protein’s epitope that has been identified having antigenic property is epitope protein RrgB 255-270 of Streptococcus pneumoniae bacteria’s pili. That epitope will stimulate immune system to produce antibody against the antigen supported by cytokine, like IL-4. This research aim is to knowing the effect of intranasal immunization epitope protein RrgB 255-270 Streptococcus pneumoniae to IL-4 level. Wistar rat’s nasal rinse sample IL-4 levels measured by ELISA method. The mean of K1 is 28,852± 18 ng/L, K2 is 20.630 ± 9 ng/L and K3 is 18.519 ± 6 ng/L. Result of Welch ANOVA test shows that p-value of this research is 0.299. That can be concluded that the effect of intranasal immunization epitope protein RrgB 255-270 S. pneumoniae give non-significant difference (p-value > 0.05).